Scattered organization of the histone multigene family and transposable elements in Synbranchus - Utsunomia, Ricardo [UNESP]; Pansonato-alves, José Carlos [UNESP]; Scacchetti, Priscilla Cardim [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Sociedade Brasileira de Genética, 2014)
The fish species Synbranchus marmoratus is widely distributed throughout the Neotropical region and exhibits a significant karyotype differentiation. However, data concerning the organization and location of the repetitive DNA sequences in the genomes of these karyomorphs are still lacking. In this study we made a physical mapping of the H3 and H4 histone multigene family and the transposable elements Rex1 and Rex3 in the genome of three known S. marmoratus karyomorphs. The results indicated that both histone sequences seem to be linked with one another and are scattered all over the chromosomes of the complement, with a little compartmentalization in one acrocentric pair, which is different from observations in other fish groups. Likewise, the transposable elements Rex1 and Rex3 were also dispersed throughout the genome as small clusters. The data also showed that the histone sites are organized in a differentiated manner in the genomes of S. marmoratus, while the transposable elements Rex1 and Rex3 do not seem to be compartmentalized in this group.
Keywords: Synbranchidae; FISH; histone; retrotransposon